Haul, Kyai, and Barakah: Integrating Ritual Theory and Sufi Psychology in Pesantren Studies - Naan Naan; Muliadi Muliadi; Muhlas Muhlas; Ahmad Jais (Living Islam: Journal of Islamic Discourses, 2025)
This article addresses a core concern of Living Islam: how lived rituals cultivate ethical selves and communal resilience. Focusing on the annual haul (memorial rite) for a Pesantren kyai, it asks why this practice endures and what it accomplishes for participants’ inner life and social ties. The study combines non-participant observation, semi-structured interviews with alumni and organizers, and document analysis conducted in Bogor between March and September 2024. The data were analyzed using ritual theory and Sufi psychology, conceptualized through the inner faculties of qalb (heart), nafs (self), and ruh (spirit), as well as the formative sequence of takhalli–tahalli–tajalli. This approach highlights four interrelated dynamics: sustained affective ties between alumni and the kyai; a “psychospiritual technology” embedded in the tahlil–pengajian–sedekah sequence that structures attention, reinforces shared meanings, and directs prosocial engagement; processes of identity renewal that strengthen alumni social capital; and moral–spiritual transformation reflected in long-term practices of prayer, charity, and teaching. Conceptually, the paper reframes the haul from commemorative rite to mechanism of ethical formation by linking patterned repetition and symbol to attentional calm, value infusion, and embodied generosity. Practically, it suggests mosque- and school-based modules that synchronize annual rituals with weekly micro-structures (mentoring, halaqah, small service projects) and proposes simple indicators regular congregational prayer, volunteer teaching hours, infaq frequency to track sustained impact. By bridging philosophical analysis with empirical description, the study clarifies how a ritual ecology translates memory into obligation, love into service, and community into a durable infrastructure for lived Islamic ethics.